2017
DOI: 10.1371/journal.pone.0172725
|View full text |Cite
|
Sign up to set email alerts
|

Regions of very low H3K27me3 partition the Drosophila genome into topological domains

Abstract: It is now well established that eukaryote genomes have a common architectural organization into topologically associated domains (TADs) and evidence is accumulating that this organization plays an important role in gene regulation. However, the mechanisms that partition the genome into TADs and the nature of domain boundaries are still poorly understood. We have investigated boundary regions in the Drosophila genome and find that they can be identified as domains of very low H3K27me3. The genome-wide H3K27me3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 69 publications
(115 reference statements)
6
62
0
Order By: Relevance
“…We chose these histone modifications not only because of their close correspondence to A and B compartments, but because of their prevalence in the Drosophila genome, such that nearly every 1 kb bin has either H3K27ac or H3K27me3 (Figure 1B, S1G). H3K27me3 is absent at H3K27ac peaks, is highly enriched at Pc-repressed loci, and shows an intermediate level of enrichment in the rest of the genome (Figure 1B), a feature that has also been reported by others (El-Sharnouby et al, 2017). We found that HiChIP for H3K27ac or H3K27me3 effectively enriched for A or B compartments respectively (Figure 1D, S1H).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…We chose these histone modifications not only because of their close correspondence to A and B compartments, but because of their prevalence in the Drosophila genome, such that nearly every 1 kb bin has either H3K27ac or H3K27me3 (Figure 1B, S1G). H3K27me3 is absent at H3K27ac peaks, is highly enriched at Pc-repressed loci, and shows an intermediate level of enrichment in the rest of the genome (Figure 1B), a feature that has also been reported by others (El-Sharnouby et al, 2017). We found that HiChIP for H3K27ac or H3K27me3 effectively enriched for A or B compartments respectively (Figure 1D, S1H).…”
Section: Resultssupporting
confidence: 84%
“…APBSs are often associated with promoters of highly expressed genes, suggesting a possible relationship between transcription and TAD border formation (Hou et al, 2012; Van Bortle et al, 2014). Several studies have found that boundaries/inter-TAD regions correlate with active chromatin (El-Sharnouby et al, 2017; Hug et al, 2017; Ulianov et al, 2016). However, whether active regions exhibit their own structure or are simply boundaries between TADs is a matter of debate due to the low resolution of currently available Hi-C datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the lack of CTCF is embryonic lethal in mammals, in Drosophila CTCF null mutants (completely lacking both maternal and zygotic CTCF) survive past the larval stage and die as late pupae with visible defects associated with Hox gene misexpression . Although Drosophila CTCF is clearly linked to functional regulatory domains in the Hox complexes, it is generally only weakly enriched at TAD boundaries . A recent paper suggests that CTCF may have a specific role in certain differentiated cell types as this study found a stronger enrichment of CTCF at TAD borders in a cell line derived from larval central nervous system than in Kc167 cells originally derived from embryos .…”
Section: How Is Domain Architecture Established Across Different Orgamentioning
confidence: 50%
“…In general, Drosophila domains lack the hotspots indicative of highly localized loop anchor elements. Instead, as illustrated in Figure c, many domains exhibit a “crown” of enhanced interaction deriving from the interaction of flanking domains . In particular, the interaction of active domains flanking inactive domains may lead to a loose loop topology based on chromatin state domains rather than on precise loop anchor elements.…”
Section: How Is Domain Architecture Established Across Different Orgamentioning
confidence: 99%
See 1 more Smart Citation